New species and records of Lycoriella Frey (Diptera, Sciaridae) from the Holarctic region - Menzel, Frank; Vilkamaa, Pekka (Zootaxa, 2021)
The following species of the genus Lycoriella Frey sensu Vilkamaa & Menzel from the Holarctic region are newly described and illustrated: Lycoriella ampla sp. n. (Canada: Ontario), L. barkalovi sp. n. (Russia: Krasnoyarsk region), L. canningsi sp. n. (Canada: British Columbia), L. eurystylata sp. n. (Canada: Quebec), L. excavata sp. n. (USA: Colorado), L. jakovlevi sp. n. (Russia: Karelia), L. kinbasketi sp. n. (Canada: British Columbia), L. longa sp. n. (USA: Colorado), L. nivicola sp. n. (Canada: Nunavut, NWT; Greenland), L. pearyi sp. n. (Greenland), L. taimyrensis sp. n. (Russia: Krasnoyarsk region) and L. tundrae sp. n. (Russia: Krasnoyarsk region). Lycoriella parva (Holmgren, 1869) is redescribed and illustrated and new faunistic records are given for some previously described species of Lycoriella. The newly described species raise the number of known species of Lycoriella from 38 to 50.